SHARIA LAW OF TAX AMNESTY IN PERSPECTIVE OF THE SOUTH KALIMANTAN MUSLIM ECONOMISTS - Mansyuroh, Firqah Annajiyah (Universitas Islam Negeri Antasari Banjarmasin, 2018)
Abstract: The rising standard of living will require an ever-increasing budget. This can be seen from the size of the Indonesian government budget for 2017, revenue in the APBN only Rp 1750.3 trillion while spending reached Rp 2,080.5 trillion. One way to increase state revenues without adding a new burden to the community is through a tax amnesty program. This policy then from the legal aspect, especially the tax amnesty legislation contains legitimacy about not enforcing the applicable laws and regulations, especially regarding administrative sanctions, criminal sanctions and legal form of tax amnesty arrangement itself. From the legal aspects of Islam, this policy of tax amnesty cannot be ignored to see the elements of maslahat and mafsadat or the dominant effect it causes in society. Therefore, author consider the Muslim economist is the right person to be consulted about the policy of tax amnesty, so that the research on tax amnesty perspectives Muslim economist South Kalimantan conducted. This research is empirical law research, which is research done in certain environment, in this case done in South Kalimantan Province. The results found are Muslim economists of South Kalimantan have a view that is divided into two in terms of tax amnesty policy, namely agree and disagree. Those who agree with this policy have the foundation of the priestly (government) policy on the people based on the benefits and considering the amount of benefits obtained compared to the non-tax amnesty.